Is the triple a P.P.T ?

Let n n and m m be positive integers, where g c f ( n , m ) = 1 gcf(n,m) = 1 , n n is odd and m m is even and n > m n > m .

In right A B C \triangle{ABC} one leg is m n \dfrac{m}{n} times the sum of the other two sides and the perimeter is 1 1 .

Multiplying each side of right A B C \triangle{ABC} by 2 n ( n + m ) 2n(n + m) we form the triple ( a , b , c ) (a^{*},b^{*},c^{*}) .

If ( a , b , c ) (a^{*},b^{*},c^{*}) is a primitive pythagorean triple, let a + b + c = 2 n m + 56 n + 186 a^{*} + b^{*} + c^{*} = 2nm + 56n + 186

and find the total number k k of values of m m for which ( a , b , c ) (a^{*},b^{*},c^{*}) is a primitive

pythagorean triple

else

enter 0 0 .


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Mar 15, 2020

a = m n ( b + c ) a = \dfrac{m}{n}(b + c) and a + b + c = 1 b + c = 1 a n m a = 1 a a + b + c = 1 \implies b + c = 1 - a \implies \dfrac{n}{m}a = 1 - a \implies

n a = m m a ( n + m ) a = m a = m n + m \implies na = m - ma \implies (n + m)a = m \implies \boxed{a = \dfrac{m}{n + m}} \implies

b + c = 1 m n + m = n n + m c = n n + m b = n ( n + m ) b n + m b + c = 1 - \dfrac{m}{n + m} = \dfrac{n}{n + m} \implies c = \dfrac{n}{n + m} - b = \dfrac{n - (n + m)b}{n + m} \implies

n 2 2 n ( n + m ) b + ( n + m ) 2 b 2 = m 2 + ( n + m ) 2 b 2 n^2 - 2n(n + m)b + (n + m)^2b^2 = m^2 + (n + m)^2b^2 \implies

n 2 m 2 = 2 n ( n + m ) b b = n m 2 n n^2 - m^2 = 2n(n + m)b \implies \boxed{b = \dfrac{n - m}{2n}} \implies

c = n 2 + m 2 2 n ( n + m ) ( a , b , c ) = c = \boxed{\dfrac{n^2 + m^2}{2n(n + m)}} \implies (a,b,c) = ( m n + m , n m 2 n , n 2 + m 2 2 n ( n + m ) ) (\dfrac{m}{n + m}, \dfrac{n - m}{2n}, \dfrac{n^2 + m^2}{2n(n + m)})

Multiplying each side of right A B C \triangle{ABC} by 2 n ( n + m ) 2n(n + m) we obtain

( a , b , c ) ( 2 n m , n 2 m 2 , n 2 + m 2 ) = ( a , b , c ) (a,b,c) \sim (2nm, n^2 - m^2, n^2 + m^2) = (a^{*}, b^{*}, c^{*}) and g c f ( n , m ) = 1 , gcf(n,m) = 1,

n n is odd and m m is even and n > m ( a , b , c ) n > m \implies (a^{*}, b^{*}, c^{*}) is a primitive pythagorean triple

a + b + c = 2 n 2 + 2 n m = 2 n m + 56 n + 186 \implies a^{*} + b^{*} + c^{*} = 2n^2 + 2nm = 2nm + 56n + 186 \implies

2 ( n 2 56 n 186 ) = 0 2 ( n + 3 ) ( n 31 ) = 0 2(n^2 - 56n - 186) = 0 \implies 2(n + 3)(n - 31) = 0 and n > 0 n = 31 n > 0 \implies n = 31

k = 31 2 = 15 \implies k = \lfloor{\dfrac{31}{2}\rfloor} = \boxed{15} .

Note: I used the following theorem below:

Let n n and m m be positive integers with n > m n > m and a = n 2 m 2 , b = 2 n m , c = n 2 + m 2 a = n^2 - m^2, b = 2nm, c = n^2 + m^2 .

The triple ( a , b , c ) (a,b,c) is a primitive pythagorean triple if and only if g c f ( m , n ) = 1 gcf(m,n) = 1 and m m and n n are not both odd.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...